2020
DOI: 10.20473/jcmphr.v1i1.20295
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Perinatal Depression in Licin Banyuwangi 2019

Abstract: Perinatal depression is a mood disorder that occurs in pregnant and postpartum women. To determine the magnitude of the risk of perinatal depression, this study uses the Edinburgh Postnatal Depression Scale (EPDS) screening tool. This study uses primary data in the form of a questionnaire to collect data on screening for depression in pregnant women and postpartum during the last 12 months. This research is an observational descriptive study with cross sectional research design. Sampling was done by cluster ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…4 In line with the results of research conducted in Banyuwangi, it also showed that 50% of pregnant women were at risk of experiencing depression. 25 Depression in pregnancy can be caused by maladaptive behavior patterns, poor coping mechanisms, problems in relationships with others, difficulties experienced and negative events, and lack of social support. 26 Based on the results of data analysis, it was found that age, education, occupation, income, parity, and anemia had no significant difference in the level of the risk of depression in the third trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…4 In line with the results of research conducted in Banyuwangi, it also showed that 50% of pregnant women were at risk of experiencing depression. 25 Depression in pregnancy can be caused by maladaptive behavior patterns, poor coping mechanisms, problems in relationships with others, difficulties experienced and negative events, and lack of social support. 26 Based on the results of data analysis, it was found that age, education, occupation, income, parity, and anemia had no significant difference in the level of the risk of depression in the third trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy and childbirth are stressful periods of life. A woman during pregnancy and the postpartum period tends to experience considerable stress due to limited physical conditions which make her have to limit activities and experience a mother's adaptation process so that during this period there is the potential for depression after psychological disorders (Putra et al, 2020).…”
Section: Introductionmentioning
confidence: 99%